Implementasi Indonesia Sustainable Palm Oil (ISPO) Petani Swadaya di Kabupaten Rokan Hulu - Aimatul Azkya; Mayarni (Indonesian Journal Publisher, 2026)
Implementation of Indonesia Sustainable Palm Oil (ISPO) for Independent Smallholders in Rokan Hulu Regency and identifying obstacles in its implementation. The implementation of Indonesia Sustainable Palm Oil (ISPO) for Swdaya Farmers in Rokan Hulu Regency is implemented through the Regulation of the Minister of Agriculture Number 38 of 2020 and strengthened by Presidential Regulation (Perpres) of the Republic of Indonesia Number 16 of 2025 concerning the Indonesian Sustainable Palm Oil Certification System. The method used is qualitative with a phenomenological approach through interviews, observations, and documentation. The analysis is based on the policy implementation theory of Van Meter and Van Horn, which includes policy target standards, resources, interorganizational relationships, implementing characteristics, socio-political-economic conditions, and implementer dispositions. The results of this study show that the implementation of ISPO on independent smallholders in Rokan Hulu Regency is still not optimal. The obstacles faced include low farmers' understanding of certification procedures and requirements, limited technical support and financing, and weaknesses in cooperative institutions in regulating and mobilizing their members. Thus, the imploement of ISPO requires strategic steps in the form of increasing the capacity of farmers' knowledge and skills, continuous assistance, providing adequate financing support, and strengthening the institutional function of cooperatives. These efforts are expected to facilitate the implementation of ISPO effectively and sustainably, so as to increase competitiveness and encourage sustainable oil palm management practices at the independent smallholder level.